P.E66Q mutation in the GLA gene is associated with a high risk of cerebral small‐vessel occlusion in elderly Japanese males. (31st May 2013) - Nakamura, K.; Sekijima, Y.; Nakamura, K.; Hattori, K.; Nagamatsu, K.; Shimizu, Y.; Yazaki, M.; Sakurai, A.; Endo, F.; Fukushima, Y.; Ikeda, S.‐I.
<x xml:space="preserve">Abstract</x> Background and purpose GLA is the causative gene of Fabry disease, an X‐linked lysosomal storage disorder resulting from α‐galactosidase A (α‐GAL) deficiency. Stroke is an important manifestation of Fabry disease, and recent epidemiological studies have indicated that up to 4.9% of young male cryptogenic stroke patients have GLA mutations. To determine the importance of GLA mutations in the general stroke population, the frequency of GLA mutations in Japanese male ischaemic stroke (IS) patients with various risk factors and ages was measured. Methods A total of 475 male IS patients (mean age 69.7 ± 12.5 years), were enrolled in this study. A blood sample was obtained to produce blood spots for measurement of α‐GAL activity. Blood samples with decreased enzymatic activity were reassayed and the entire GLA gene was analyzed by direct DNA sequencing if α‐Gal A activity was consistently low. Results α‐Gal A activity was decreased in 10 men, five of whom (1.1%) had the GLA gene mutation, p.E66Q. All IS patients with p.E66Q mutation had substantial residual α‐Gal A activity, in contrast to patients with classic‐type Fabry disease. Clinically, all patients with p.E66Q mutation were > 50 years old and had multiple small‐vessel occlusions (lacunar infarctions). Statistical analysis using Fisher's exact test showed the allele frequency of GLA p.E66Q in patients with small‐vessel occlusion to be significantly higher than that in the general Japanese population [odds ratio (OR) = 3.34, P = 0.025). Conclusions GLA p.E66Q mutation is a genetic risk factor for cerebral small‐vessel occlusion in elderly Japanese males.